A tumor multicomponent targeting chemoimmune drug delivery system for reprograming the tumor microenvironment and personalized cancer therapy. Issue 7 (July 2018) - Sau, Samaresh; Tatiparti, Katyayani; Alsaab, Hashem O.; Kashaw, Sushil K.; Iyer, Arun K.
Highlights: Nanoparticle-based immunotherapy is an emerging platform for cancer. Tumor multicomponent targeting is a rational approach for achieving clinical success. Copper-free click chemistry is highly versatile for engineering multifunctional nanoparticles. Nanomedicines can be multifunctional drug delivery agents for cancer therapies. However, they have faced several challenges in clinical trials owing to poor targeting ability, insufficient tumor penetration, difficulty in synthesis and scale up, and limited understanding of interactions between a tumor and nanoparticles. In this regard, tumor muticomponent targeting drug delivery systems are a rational approach for developing tumor-site-specific therapeutics. One of the goals is to arrive at a ready-to-configure, combinatorial, reagent-free click-chemistry-based tumor multicomponent targeting nanoparticle library. The nanoparticles can be co-loaded with drugs, genes and imaging agents, surface decorated with varying targeting ligands that can home to varying tumors and/or tumor multicomponents. This library of nanocarriers could be utilized for early tumor diagnosis and therapy based on individual patient needs for personalized medicine, with a high degree of success in the clinic. Teaser: Nanoparticle library engineered with tunable size, shape, and geometry will provide a better idea of targeting multicomponent of tumor microenvironment consisting of epithelial cells, tumor hypoxia, tumor immune cells and angiogenic blood vessels.